2016
DOI: 10.1016/j.clim.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of inhibitors of the PI3K/mTOR pathway on the expansion and functionality of regulatory T cells

Abstract: The PI3K/mTOR pathway is commonly deregulated in cancer. mTOR inhibitors are registered for the treatment of several solid tumors and novel inhibitors are explored clinically. Notably, this pathway also plays an important role in immunoregulation. While mTOR inhibitors block cell cycle progression of conventional T cells (Tconv), they also result in the expansion of CD4(+)CD25(hi)FOXP3(+) regulatory T cells (Tregs), and this likely limits their clinical antitumor efficacy. Here, we compared the effects of dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…PI3K/AKT, p38 and JNK MAPKs were also involved in the HSP70-dependent activation of Tregs, while the MAPK ERK1/2 had a much lower impact on Tregs [30]. PI3K inhibition alone might exert antitumor effects without the detrimental selective expansion of Tregs associated with mTOR inhibition [27]. Similar to these findings, we observed the activation of PI3K/AKT and mTOR after stimulation with H/R-DEXs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…PI3K/AKT, p38 and JNK MAPKs were also involved in the HSP70-dependent activation of Tregs, while the MAPK ERK1/2 had a much lower impact on Tregs [30]. PI3K inhibition alone might exert antitumor effects without the detrimental selective expansion of Tregs associated with mTOR inhibition [27]. Similar to these findings, we observed the activation of PI3K/AKT and mTOR after stimulation with H/R-DEXs.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, a recent study demonstrated that phosphatidylinositol 3-kinase (PI3K)/AKT, p38 and c-Jun N-terminal kinase (JNK) mitogen-activated protein kinase (MAPK) were involved in HSP70-dependent activation of Tregs [30]. PI3K inhibition alone might offer antitumor efficacy without the detrimental selective expansion of Tregs associated with mTOR inhibition [27]. To verify the transport and function of HSP70, the co-culture of DEXs and naïve T cells was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mTOR and dual PI3K/mTOR inhibitors have been shown to induce Tregs’ expansion and their immunosuppressive activity, thus correlating with a poor prognosis in cancer patients [123]. Encouragingly, Huijts and her group showed that the PI3K inhibition alone allows for the expansion of Tregs, but without affecting their overall suppressive activity [124]. …”
Section: Implications In Cancer Immunotherapymentioning
confidence: 99%
“…Rapamycin is a potent autophagy inducer in addition to its ability to block mTORC1 141. Recent studies show that mTORC1 regulates T-cell differentiation and its activation blocks FoxP3, a key transcription factor for Treg 139,142. Thus, rapamycin blockade of mTORC1 likely induces a variety of regulatory pathways in SEB-stimulated cells, including autophagic removal of damaged mitochondria, induction of functional Treg, downregulation of apoptosis, inflammatory cytokines, and T-cell proliferation.…”
Section: Repurposing Of Us Food and Drug Administration (Fda)-approvementioning
confidence: 99%